CLINICAL COURSE, LONG–TERM EFFECTS AND OUTCOMES HEPATITIS A IN CHILDREN - V.F. Uchaikin; T.V. Cherednichenko; O.B. Kovalev (Педиатрическая фармакология)
Hepatitis A — the most widespread virus disease of the liver in human. In the general structure of virus hepatitis no less than 90% makes hepatitis A. Hepatitis A is usually a self' limiting disease and infection confers lifelong immunity. However, the hepatitis A has of great clinical importance in children. Hepatitis A virus causes both acute disease and asymptomatic infection. The disease is usually asymptomatic in young children. Acute hepatitis A usually lead to full liver recovery during 2–3 months or protracted hepatitis A — a condition in which the virus is slow to clear and the liver takes longer than usual to regain its normal function and can last for up to 5–6 weeks. Hepatitis A does not cause chronic infection, but can lead to some complications. From 1158 children treated for hepatitis A in our clinic, 85,7% has developed affection biliary tracts, 76,7% — affection duodenum, 4,5% — was registered residual liver fibrosis. So, Hepatitis A is a serious disease and can lead to considerable clinical and economical burden. Introduction the mass vaccination programme in Russia will lead to decrease incidence, long'term effects and complications of Hepatitis A in children.Key words: hepatitis A, children, outcomes, burden, vaccination programme.